Qualidade do leite tipo C produzido e comercializado no Rio Grande do Norte - Bezerra, Nicholas Morais (Universidade Federal Rural do Semi-Árido, 2009)
With the purpose of to evaluate the quality of the milk kind C produced and sold in Rio Grande do Norte, Were collected 75 samples of milk distributed in the principal producing regions of the state (Natal, Mossoró e Caicó). Among then are the milk sold in retail and the milk distributed by the program of the government. Were analysed the physicalchemical characteristics by the ultrasound machine called Ekomilk® and in the microbyology researches was made the couting of colonies of bacterias mesophilics, psychrotrophics e Staphylococcus coagulase positive. In Natal, the milk seemed inferior than the milk of the others regions in physical and chemical meaning, as a result we concluded that in this region there was fraud related by addition of water, we also supected a high change in consequence of the mastitis of the herd, and it was noticed the change in the total solids (fat, lactose and protein), probablly because of the effect of the microorganisms presents in a big amount in the milk of this area. In Mossoró we also saw addition of water in the milk, in spite of so much lower than if compared with the milk of Natal. Caicó just showed the fat above the level of the level imposed by the legislation. The milk distributed by the government was similar to the milk sold in a retail trade in all of their characteristics. The milk in the state seemed very bad because most of then showed unless one ilegal characteristic.
Quality of milk type C produced and marketed Rio Grande do Norte
Keywords: Milk; Quality; Microbiologic; physical-chemical; Leite; Qualidade; Microbiológico; Físico-Químico; CIENCIAS AGRARIAS::MEDICINA VETERINARIA